Phenomenology Analysis of the Meaning of Healthy Living on Alternative Medicine Practices - Eny Pemilu Kusparlina; Ishomuddin; Sukmana, Oman; Sunaryo, Sidik (International Journal of Law and Society, 2023)
A healthy life is a sense of well-being due to fulfilling all needs within reasonable limits so that physical and mental health can be realized from various life stages. People still interpret healthy life according to their thoughts and understanding, which cannot be separated from beliefs, family values, and culture; they still choose to use alternative medicine instead of modern medicine. This research aims to understand the community's actions in interpreting a healthy life that prefers alternative medical practices compared to modern medical practices. The research method used is a qualitative approach with a phenomenological research type. This study used a purposive technique with four people as subjects who used alternative medicine facilities. Data collection techniques using observation, interviews, and documents. The data analysis method used is proprietary data analysis to analyze field data, while the data validation method uses triangulation. The results of this study are based on the dimensions of awareness, experience, suggestions, believed; the meaning of a healthy life with alternative medicine is not only physical (physical) health but non-physical (spiritual) health as well. Alternative medicine is a unique and holistic treatment. The process of creating a healthy life begins with the human element itself, which starts with the seeds, weight, and calves in the process of the human life cycle from birth to death in behaviour and science.